Training and Transformation: Implication of Teacher Training in Community Schools of Gandaki Province - Bhandari, Nagendra Bahadur; Paudel, Pitambar; Baral, Rohit Prasad; Sapkota, Narayan Prasad; Yadav, Anisha (Prithvi Journal of Research and Innovation, 2022)
This paper analyses the implication of Teachers' Professional Development (TPD) training in pedagogical transformation in community schools in Gandaki Province, Nepal. It followed sequential explanatory mixed methods research design. The sample size of this study comprised selected 45 secondary level TPD trained teachers purposively from Kaski, Tanahu, and Syangja Districts of Gandaki Province from five schools from each district. The quantitative data were collected through questionnaire survey with teachers and the qualitative data were collected through Focus Group Discussions with trainers and head teachers separately. The analysis of data reveals that pedagogical transformation through training is not satisfactory. For the effective implementation of training knowledge and skill of training, the coordination among all the stakeholders needs to be harmonious. The training curricula, trainers’ knowledge and skill, and teaching context should be updated and improved as per the current social situation. Besides, the teachers’ motivation and devotion are the key elements for adequate pedagogical transformation. The study concluded that regular monitoring with a reward and punishment policy can implement the training knowledge and skill for pedagogical transformations.